2010
DOI: 10.1038/gt.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

AAV-P125A-endostatin and paclitaxel treatment increases endoreduplication in endothelial cells and inhibits metastasis of breast cancer

Abstract: Endostatin potentiates the antimitotic effects of paclitaxel (taxol) on endothelial cells (ECs). P125A-endostatin and taxol-treated ECs showed multipolar spindles and nuclear lobulation, leading to mitotic catastrophe and cell death. Induction of nuclear abnormalities was found to be dependent on b-catenin levels as wnt-mediated overexpression of b-catenin reversed the changes in nuclear morphology. These results prompted us to investigate whether antiangiogenic gene therapy and paclitaxel chemotherapy can syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Increasing the delivery of Taxol, an anti-proliferation drug, to endothelial cells through MB-mediated US therapy will reduce the cell proliferation, resulting in starvation of the tumor and prohibiting increased tumor growth. Specifically, Taxol inhibits microtubule dynamics of cytoskeletal elements resulting in mitotic arrest (Subramanian, 2011). Additional positive antitumor effects of MB-mediated US therapy is the ability to increase vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the delivery of Taxol, an anti-proliferation drug, to endothelial cells through MB-mediated US therapy will reduce the cell proliferation, resulting in starvation of the tumor and prohibiting increased tumor growth. Specifically, Taxol inhibits microtubule dynamics of cytoskeletal elements resulting in mitotic arrest (Subramanian, 2011). Additional positive antitumor effects of MB-mediated US therapy is the ability to increase vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…A phase III clinical trial on 493 stage IIIB and IV non-small cell lung carcinoma (NSCLC) patients showed that the addition of endostar to a vinorelbine/cisplatin regimen resulted in significant and clinically meaningful improvement in response rate, median time to progression, and clinical benefit rate compared to the chemotherapeutic regimen alone [ 4 ]. Regarding breast cancer, in vivo studies showed that the combination of paclitaxel and P125A-endostatin inhibited mammary cancer growth, delayed the onset of multifocal mammary adenocarcinomas, decreased tumor angiogenesis, increased the survival of treated mice in the prevention model, and inhibited lung and lymph node metastasis in the intervention model [ 5 ]. Sun et al also reported that the tumor-inhibiting effect of the paclitaxel-cisplatin (TP) regimen combined with recombinant human endostatin on breast cancer is better than that of the TP regimen alone in xenograft-bearing nude mice [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel interferes with the cell cytoskeleton by altering microtubule rearrangement [11]. Paclitaxel was the first taxane used in clinical trials and found to be used with ovarian and breast cancers resistant to chemotherapy and has been used in vivo studies for inhibiting mammary cancer growth, delaying mammary adenocarcinomas, and decreasing tumor angiogenesis [12]. Usage of paclitaxel with radiation, in initial therapy, was shown to improve survival [13].…”
Section: Introductionmentioning
confidence: 99%